2019
DOI: 10.1002/jor.24202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduced tip‐apex distance on helical blade fixation—a biomechanical study

Abstract: Migration profile of helical blades differs from conventional screw design. Tip‐apex distance (TAD) greater than 25 mm is associated with early failure in hip screws. This study investigates the effect of a reduced TAD on helical blade fixation. Six pairs of human femoral heads were used. Bone mineral density (BMD) was determined by pQCT. Local bone quality was evaluated by breakaway torque. Helical blades were implanted with TAD of 20 mm (normal) and 6 mm (reduced). Specimens were cyclically tested under prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Figure 6 shows the protrusion of the Conventional-Blade on the surface of the polyurethane foam block following the push-in test. According to Nikoloski et al and Lenz et al, the blade type behaves differently to the lag screw type, and placement too close to the subchondral bone may lead to penetration through the head 23 , 24 ; the result of our push-in test supports their finding. In addition, this protrusion may worsen owing to excessive intraoperative insertion force and postoperative weight-bearing and may lead to ‘cut through’, i.e.…”
Section: Discussionsupporting
confidence: 79%
“…Figure 6 shows the protrusion of the Conventional-Blade on the surface of the polyurethane foam block following the push-in test. According to Nikoloski et al and Lenz et al, the blade type behaves differently to the lag screw type, and placement too close to the subchondral bone may lead to penetration through the head 23 , 24 ; the result of our push-in test supports their finding. In addition, this protrusion may worsen owing to excessive intraoperative insertion force and postoperative weight-bearing and may lead to ‘cut through’, i.e.…”
Section: Discussionsupporting
confidence: 79%
“…A lower TAD limit is equally debated within the literature. A biomechanical study from Lenz et al demonstrated no significant differences in number of cycles to failure between cadavers with normal (20 mm) and reduced (6 mm) TAD; however, the clinical relevance is yet to be determined [ 29 ]. Each intramedullary nailing system may have unique TAD requirements, as opposed to the one-size-fits-all approach used today.…”
Section: Discussionmentioning
confidence: 99%